On an upper bound for the number of characteristic values of an operator function - Radzievskii, G. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We prove a theorem on an upper bound for the number of characteristic values of an operator-valued function that is holomorphic and bounded in a domain. This estimate is similar to the well-known inequality for zeros of a number function that is holomorphic and bounded in a domain. We derive several corollaries of the theorem proved, in particular, a statement on an estimate of the number of characteristic values of polynomial bundles of operators that lie in a given disk.